Challenges to Saudi medical education in the third millennium - Fahad A Al-Muhanna (Wolters Kluwer Medknow Publications, 2009)
Medical education began in Saudi Arabia in 1969 when King Saud University, the first medical school was established. Since then globalization has brought numerous challenges. In this paper, we review the status of medical education and its expected future projects.